Grenzen des Wettbewerbs im Gesundheitswesen - Ingmar Kumpmann (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2008)
– Many health economists demand more competition in the health care system. They focus on the competition between sickness funds for insured and the competition between health care providers for contracts with sickness funds. But they neglect the competition between health care providers for patients which is crucial for medical quality. This third field of competition is in conflict with the two former fields. The empirical evidence concerning the effects of competition on cost and quality is also ambiguous. Thus the mere claim for "more competition" does not do justice to the high complexity of the health care system.
urn:nbn:de:gbv:3:2-6014
Keywords: I11; I18; D61; 330; health care system; competition; free choice of medical practitioner; Gesundheitswesen; Wettbewerb; Gesundheitsökonomik; Gesetzliche Krankenversicherung; Ärzte; Dienstleistungsqualität; Patienten; Deutschland